HUBUNGAN PENDAPATAN DAN POLA KONSUMSI MASYARAKAT PERDESAAN DAN PERKOTAAN DI SULAWESI UTARA - Brigita Kezia Maria Kumaat; Sherly Gladys Jocom; Theodora M. Kathiandagho; Tommy Ferdy Lolowang; Agnes Estephina Loho (Halu Oleo University, 2024)
The study aims to determine the relationship between income and consumption patterns of rural and urban communities in North Sulawesi. Data analysis in this research was carried out descriptively. The descriptive research method is a research method that provides a general description of the object being studied, such as looking at the movement of each research variable, one of which is by describing the movement of each research variable in the form of a table or graph. The consumption patterns of rural and urban communities show diversity. On average, between 2018-2022, rural communities in North Sulawesi, except for rural areas in Bitung City, allocate more expenditure to non-food consumption than to food consumption. Furthermore, of the eleven districts and four cities in North Sulawesi, only urban communities in Minahasa Regency, Talaud Islands, Manado City, Tomohon City and Kotamobagu City have a greater percentage of expenditure on non-food consumption than food consumption. This phenomenon indicates that apart from income, there are other factors that influence people's consumption patterns in both rural and urban areas in North Sulawesi.